HIDROGEOQUÍMICA DE UM AQUÍFERO CÁRSTICO EM MINAS GERAIS, BRASIL - Silva, Adelbani Braz da; Gimena, Emílio Custódio; Cruz, Waldemir Barsbosa da; Escondino, Paulo Cyro Baptista (Águas Subterrâneas, 1982)
Resumo não disponível.